2018
DOI: 10.1194/jlr.m089771
|View full text |Cite
|
Sign up to set email alerts
|

ABHD5 stimulates PNPLA1-mediated ω-O-acylceramide biosynthesis essential for a functional skin permeability barrier

Abstract: Mutations in the genes coding for patatin-like phospholipase domain-containing 1 (PNPLA1) and α/β-hydrolase domain-containing 5 (ABHD5), also known as comparative gene identification 58, are causative for ichthyosis, a severe skin barrier disorder. Individuals with mutations in either of these genes show a defect in epidermal ω-O-acylceramide (AcylCer) biosynthesis, suggesting that PNPLA1 and ABHD5 act in the same metabolic pathway. In this report, we identified ABHD5 as a coactivator of PNPLA1 that stimulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 41 publications
(59 reference statements)
3
32
0
Order By: Relevance
“…5B). Recent studies (35,36) reported that CGI-58 recruits PNPLA1 to LDs, raising the possibility that CGI-58 promotes the activity of multiple PNPLA family members by stabilizing their interactions with LDs and access to lipid substrates. This possibility is consistent with Lord et al, (37) who showed that CGI-58 activates lipolysis independently of ATGL.…”
Section: Discussionmentioning
confidence: 99%
“…5B). Recent studies (35,36) reported that CGI-58 recruits PNPLA1 to LDs, raising the possibility that CGI-58 promotes the activity of multiple PNPLA family members by stabilizing their interactions with LDs and access to lipid substrates. This possibility is consistent with Lord et al, (37) who showed that CGI-58 activates lipolysis independently of ATGL.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to systemic or epidermis-specific CGI-58 gene deletion, systemic ATGL knockout mice do not develop a defective skin permeability barrier despite epidermal TG accumulation suggesting an ATGL-independent function of CGI-58 in the skin [ 212 , 213 ]. In fact, very recently CGI-58 has been shown to stimulate ω-O-acylceramide synthesis in the skin that depends on protein interaction with PNPLA1, a close homologue of ATGL [ 214 ]. The role of PNPLA1 in ω-O-acylceramide synthesis and skin barrier function is discussed in detail within this Special Issue by Hirabayashi et al [ 215 ].…”
Section: What We Have Learnt From Mouse Models and Patientsmentioning
confidence: 99%
“…α/β hydrolase domain-containing protein 5 (ABHD5) has been identified to interact with PNPLA1 as a coactivator. It could be easily inferred that ABHD5 mutations can decrease epidermal ω-О-acylceramide synthesis, thereby causing ichthyosis [85]. Comparative gene identification-58 (CGI58) deficiency also impairs ω-О-acylceramide synthesis with severe barrier defects in Cgi58-deficient mice [86].…”
Section: Skin Lipidsmentioning
confidence: 99%